Single-phase series active conditioner for the compensation of voltage harmonics, sags, swell and flicker - Carneiro, H. (2011)
Simulation and experimental results shown on this paper describes the performance of a developed Single-Phase Series Active Conditioner that regulates the voltage being delivered to a load. This Custom Power device is a solution for power quality issues related with voltage amplitude variations, which are responsible for innumerous flaws in industrial processes which brings with it high financial losses. The Single-Phase Series Active Conditioner is a back-to-back converter, composed by two power converters sharing a common DC link. One of the converters is series connected to the electrical grid, whereas the other one is shunt connected. The first is used to compensate load voltage, and the second to regulate the DC link voltage. This paper shows the results obtained with the Series Active Conditioner in Sag, Swell and Flicker events, and also Voltage Harmonics compensation, in order to deliver to the load a sinusoidal voltage, at nominal amplitude.